Female sexual function varies over time and is dependent on partner-specific factors: a population-based longitudinal analysis of six sexual function domains - A. Gunst; D. Ventus; A. Kärnä; P. Salo; P. Jern (Cambridge University Press, 2022)
Background
Most studies examining female sexual functions (FSFs) have used cross-sectional designs, not allowing for studying temporal stability and possible relationships between different FSFs over time. Our aim was to study these relationships using a longitudinal approach.
Method
The study sample consisted of 2173 Finnish women from two large-scale, population-based data collections 7 years apart. The Female Sexual Function Index was used. Analyses were further conducted separately for women in different relationship constellations.
Results
Standardized autoregressive paths ranged from 0.136 (sexual satisfaction) to 0.447 (orgasm function) in the full sample, suggesting that most of the variance in FSF was explained by something other than previous function. Orgasm, desire and satisfaction were the strongest predictors of other functions in the full sample and for women in the same relationship at both time points (higher orgasm function predicted higher function in other domains; greater sexual desire and satisfaction predicted lower function in other domains), however, with small effects sizes. For single women, orgasm function and sexual desire were the only significant autoregressive paths. Significant unidirectional cross-domain paths were found for women in the same relationship at both time points. One significant cross-domain path, not confirmed as unidirectional, was found for single women.
Conclusions
FSFs varied considerably over 7 years and relationship status was of importance when assessing temporal stability and cross-domain effects. Our results advocate tailored psychobehavioural treatment interventions for female sexual dysfunctions that take partner-specific factors into account.